1981
DOI: 10.1080/00288233.1981.10420882
|View full text |Cite
|
Sign up to set email alerts
|

Environmental influences on hogget lambing performance and the relationship between hogget and two-tooth lambing performance

Abstract: The influence of birth-rearing rank, dam age, and live weight on hogget traits and lambing performance are described for 15 731 Romney ewe hoggets recorded in the Department of Lands and Survey Romney Breeding Scheme over 5 years (1972)(1973)(1974)(1975)(1976). Two-year old lambing performance of the 8 157 hoggets retained in the years 1973-1977 was investigated for effects of previous lambing as a hogget. Dam age and birth-rearing rank effects were present in all hogget traits-lamb weaning weight, September (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
2

Year Published

1983
1983
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 18 publications
0
7
2
Order By: Relevance
“…The values were, however, higher than those found for some Romney hoggets (Hight et al 1973;Baker et al 1981;Meyer 1981;McCall & Hight 1981;Moore et al 1983) despite having a similar liveweight. This may reflect a better mating performance of Dorset compared to Romney hoggets.…”
contrasting
confidence: 66%
See 1 more Smart Citation
“…The values were, however, higher than those found for some Romney hoggets (Hight et al 1973;Baker et al 1981;Meyer 1981;McCall & Hight 1981;Moore et al 1983) despite having a similar liveweight. This may reflect a better mating performance of Dorset compared to Romney hoggets.…”
contrasting
confidence: 66%
“…Mating and lambing of hoggets has beneficial effects on subsequent lifetime reproductive performance and lamb survival, with the effects being especially apparent in 2-year-old ewes (Hight & Jury 1976;Baker et al 1981;McCall & Hight 1981;McMillan & McDonald 1983;Moore et al 1983). Whereas some workers found no effects of the lambing of hoggets on growth rates and weaning weights of lambs born in subsequent years (Keane 1974;McMillan & McDonald 1983), other workers have found higher growth rates and weaning weights (Baker et al 1981), and higher milk production as 2-year-olds (McGloughlin & Crowley 1971).…”
Section: Introductionmentioning
confidence: 96%
“…Overseas, the practice has been shown to increase lifetime reproductive performance in several breeds (Dyrmundsson 1973). An improvement in the 2-year-old reproductive performance of previously lambed Waihora Romney ewes has been reported (McCall & Hight 1981), but the effects of hogget lambing per se could not be determined because ' no control ewes remained unjoined. Hogget lambing under North Island hill country conditions had no effect on 2-year-old lambing (R. L. Baker, pers.…”
Section: Introductionmentioning
confidence: 97%
“…In contrast, in the mature ewe the aim is generally not to increase conceptus-free liveweight. It is likely that the affects of poor nutrition in pregnancy would be more pronounced in the hogget than in the mature ewe, as hoggets tend to give birth to relatively lightweight lambs (McMillan 1983;McMillan & McDonald 1983) which display low survival rates (McCall & Hight 1981;Craig 1982;McMillan 1983;McMillan & McDonald 1983;Moore et al 1989). Interestingly, Wallace et al (1996Wallace et al ( , 1997 and Wallace (2000) reported that a very high level of hogget nutrition using concentrates increased foetal loss via spontaneous non-infectious abortion, decreased lamb birthweight and colostrum production, and increased neonatal losses.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, hoggets were not weaned until January, which would have limited the time available for "low" group hoggets to achieve adequate two-tooth mating weights. Interestingly, field studies to date have not reported decreased two-tooth reproductive performance from hogget lambing (McCall & Hight 1981 ;Craig 1982;McMillan & McDonald 1983;Moore et al 1989).…”
mentioning
confidence: 99%